Analysis of the Influence of Structural Parameters of Coupling-Type Casing Threads on Joint Connection Strength - Chao, Lining; Tang, Jiarui; Wang, Heping; Wang, Qiang; Yang, Xiaolong; Tang, Chen; Li, Tianzhou (Scientific Journal of Technology, 2025)
Casing drilling technology originates from mining wire-line coring technology. It uses casing as the drill string to perform drilling and casing running simultaneously without the need for pulling out. This technology can solve downhole accidents in complex formations and is suitable for large-sized boreholes. However, due to the characteristics of the casing, the joint connection strength is weak, the performance is poor, and the thread stress is complex and uneven, making it the weakest link of the pipe string. To fill the gap in the existing research on the influence of thread structure on joint strength, this paper establishes a mechanical analysis model for casing joint threads, explores the influence laws of two factors, namely variable tooth width and shoulder clearance, on the torsional resistance performance of casing threads, and provides a reference for the research on the structural optimization of casing joint threads. The research results show that reducing the tooth width at the small end of the male thread and increasing the tooth width at the small end of the female thread can balance the maximum stress of the male and female threads and improve the load-bearing capacity of the threads. However, a further increase in the tooth width ratio will lead to excessive stress at the small end of the male thread, making it the main failure part. With the increase of shoulder clearance, the stress begins to decrease, and the maximum stress shifts from the female shoulder to the first thread turn. However, an excessively large clearance will reduce the load shared by the shoulder and cause an increase in the overall stress of the thread.